Design and Evaluation of an Application Software for Informal Peer Group Learning - Jasinghe, Prasadi (My University, 2012)
Laptop computers are being increasingly used as a mediation artifact for informal peer group learning. However, since students often have informal peer group discussions at outside locations from the institute, they find it difficult to use several laptop computers interactively within a group discussion. Therefore, it is common to see that students only use single laptop computer for their group discussions. This not only under utilizes available computer resources but also reduces the benefits of group learning. We have developed an application software to overcome these limitations. In addition to that, we evaluated the tool for its usability and effectiveness when it is used for real world informal peer group discussions by university student groups. The results depicts that the tool can successfully be used for informal peer group learning.